Meanings of indefiniteness in the Quranic style - a semantic study (Journal of the College of Basic Education, 2022)
The composition discloses the intent and meanings of negation in the Holy Qur’an. And it is a lotglorification; praise and camping; And the end, the intimidation, and the desire; And be of him with belittlement rebukeInsult, contempt, mockery and intimidation. The suffixes supporting the accusative help clarify the meaningIn description, conjunction, plural, individuals, formulas, weights, or letters and tools.The style discloses generality, inclusion, specificity, designation, emphasis, delay, and releaseprevalence, characterization, elaboration, diversification and expansion; And other virtues of disguise and its meaningsin his miraculous style.The research relied on the opinions of scholars and the people of the Qur’an, and we analyzed and interpreted the surahsQuranic, dividing it into glorification and glorification; humiliation and reprimand; And reduce and multiply and in general